The Structural Analogy Between Text and Body: A Study in the Ontology of Writing in Roland Barthes (Damascus University Journal of arts and humanities sciences, 2026)
Barthes juxtaposed the structure of the world as it exists with the epistemological structure of language. This juxtaposition is not a mere rhetorical imposition but is driven by a clear methodological vision that claims deconstructing language leads to deconstructing the very structure of the world. Thus, semiotics, in this sense, is merely the study of how language shapes the world.Similarly, he drew an analogy between the text and the body in terms of determinacy and uniqueness. The body, as an ontological concept, first signifies that a thing does not exist—nor can it be described as such—until it is embodied. Second, it is a historical process that is never entirely detached from its temporal context and spatial conditions. Consequently, the body is a cultural entity, a symbolic and historical construct with its own sites of desire and longing. It is also a code that encapsulates vast ancestral genetic lineages—and so is the text. This analogy is not merely a metaphor but an analytical model capable of uncovering the hidden dynamics of cultural discourse. This opens new horizons for understanding various texts as existential acts before they are aesthetic artistic phenomena.In this research, we will attempt to provide a deconstructive reading of this semiotic claim, aiming to reach findings that may contribute to a deeper understanding of our contemporary world.
Keywords: Structural Analogy; Text; Body